GALLERY WALK TECHNIQUE IN IMPROVING STUDENTS SPEAKING SKILL AT SMP UNISMUH MAKASSAR - Asyra Qamra Bahar; Hasnawati Latief; Yassir Mallapiang (FKIP Unismuh Makassar, 2022)
This research aimed at finding out whether or not the implementation gallery walk technique in improve the students speaking skill term of accuracy and fluency at the SMP UNISMUH Makassar. This research was conducted through pre-experimental method. The populasi of this research consisted of one class of the second grade and the sample of the research, the researcher took VIII A 1 class which consisted of 23 students at High School SMP UNISMUH Makassar, year 2019/2020.In collecting data, the researcher gave a speaking test, the speaking test help into two steps, there were pre-test and post-test, while to analyzed data , the researcher used (t)test. The findings of this research showed that the mean score in pre-test in term of pronouncation was (53,30) and post-test was (76,56). The mean score in pre-test in term smoothness was (51,86) and post-test was (80,04). And the total result of pronouncation and smoothness in pre-test or X1 was (53,39) and the post-test or X2 was (76,56). So, this is showed students got improvement in thier speaking after being taught through gallery walk technique, the students ability in speaking english became better than befofe.